PENINGKATAN KEMAMPUAN BERPIKIR SISWA SD DALAM IPA MELALUI PENERAPAN GUIDED DISCOVERY - Woro Sri Hastuti (Jurnal Penelitian Ilmu Pendidikan, 2010)
The aim of this research was to improve students' thinking ability in science through the application of guided discovery. This research is a kind of class room action research. The subject is all of students in fifth-grade SD N Delegan II Dinginan Prambanan Sleman Yogyakarta. Before doing first action, researcher was improving lesson planning and student worksheet which is based on guided discovery strategies that is used in the action. This collaborative research consists of researcher, observer, and teacher. The students' thinking was obtained from observation data, scientific activity report, and formative test. The kind of data analysis technique is descriptive statistic. Implementating strategies in guided discovery that used open ended students' worksheet media, plus giving reward, giving the same chance of all students to be active, and giving individual responsibility in each group in presentation & discussion sessions, had improved the ability of students' thinking from sufficient into good category. Keywords: Thinking Ability, Science, Guided Discovery, Elementary School